Identification and RNAi‐based functional analysis of chitinase family genes in Agrotis ipsilon. Issue 10 (12th July 2022) - Li, Daqi; Zhang, Jianqin; Yang, Yang; Liu, Jiao; Lu, Junjiao; Ren, Meifeng; Abbas, Mureed; Zhu, Kun Yan; Zhang, Jianzhen
Abstract: BACKGROUND: Chitin is a major component in the extracellular matrix of insects, and its metabolism largely affects insect development and molting. As essential degradative enzymes, chitinases are encoded by multiple genes that differ in size, expression pattern and function in insects. However, our limited knowledge on the functions of different chitinases in Agrotis ipsilon has prevented our application of new technologies to target these genes as new pest management strategies. RESULTS: We revealed 11 full‐length complementary DNA sequences of chitinase genes ( AiChts ) from A. ipsilon transcriptome. Although the domain architecture of these chitinases varied greatly, they all contained at least one chitinase catalytic domain. Developmental stage‐ and tissue‐dependent expression profiles showed that most AiCht s had the highest expression in the pupal stage. Furthermore, AiCht2, AiCht6, AiCht7 and AiCht10 were mainly expressed in the integument, whereas AiCht8 and AiCht‐h had the highest expression in the midgut. The RNA interference (RNAi) experiment revealed that knockdown of AiCht10 or the imaginal disc growth factor gene ( AiIDGF ) induced high larval mortality. Larvae failed to shed the old cuticle during molting after the injection of double‐stranded RNA targeting AiCht10 (ds AiCht10 ), whereas the larval bodies shrunk and blackened after the injection of dsRNA targeting AiIDGF (ds AiIDGF ). CONCLUSION: Our results revealed for the first time the important functions of AiCht10 and AiIDGF in A. ipsilon . These genes are essential for larval development, and can potentially serve as new targets for RNAi‐based pest management. © 2022 Society of Chemical Industry. Abstract : Eleven full‐length complementary DNA sequences of chitinase family genes were identified from Agrotis ipsilon based on transcriptomic data, which differ in size, domain architecture and gene expression pattern. RNA interference‐based knockdown of AiCht10 or AiIDGF induced high mortality in larvae, ds AiCht10 retarded molting, whereas ds AiIDGF induced bodies to shrink and blacken.